LaunchPad CadOperator. - Snoonian, Deborah (Architectural Record, 2004)
The article focuses on LaunchPad CadOperator, a combined software/hardware package which aims to slash drafting time by 50 percent or more. A specialized keyboard and mouse device simplifies repetitive tasks and reduces the number of keystrokes needed for common operations. The software allows users to create shortcuts for, and libraries of, specialized "blocks," hatch patterns, color combinations, layering rules and styles, line weights, and other popular drafting tasks. Training videos and online tutorials are also available to bring users up to speed, literally.